The Effect Of Snowball Throwing Method In Reading Comprehension Of Narrative Text At Grade Ten Of SMA Negeri 1 Siantar - Gretha Ruth Winda Simanjuntak; , Dumaris E. Silalahi; Rudiarman Purba (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The purpose of this research is to determine the more significant influence of the Snowball Throwing method on the reading comprehension of narrative text for class X SMA NEGERI 1 SIANTAR students. This research uses an experimental design. The problems in this research are the problems of students who have low reading comprehension abilities, students who are not familiar with the vocabulary in the text, and students who do not understand how to find the main idea in the narrative text they read. This research uses an experimental design, meaning that there is a certain experiment that is applied to a population or sample. And the population of this study were two classes, namely students in classes X-3 and X-4, totaling 60 students. The sample size is 30 students in each class. The control group used a textbook while the experimental group was taught using the snowball throwing method. In this study, data analysis showed that the average post-test score for the experimental group was 76, while the score for the control group was 64.16. The influence of the Snowball Throwing Method is more significant than without using the Snowball Throwing Method on the Reading Comprehension of class X SMA NEGERI 1 SIANTAR students in narrative texts. This is proven by the t test of 3.56 and the t table value of 2.001 and df = 58 (Nx+Ny-2 = 30+30-2 = 58). The t test value is greater than the t table value (t test > t table). Therefore the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.